Outcomes after surgery for children in Africa (ASOS-Paeds): a 14-day prospective observational cohort study - Elhadi, Muhammed; Bisegerwa, Ronald; Munlemvo, Dolly M.; Abdullahi, Lawal Barau; Adegoke, Paul Aderemi; Adeoye, Ibukunoluwa; Adjei, Esther; Ahmed, Nidal Youseef Altaher Aboh; Aji, Narjiss; Ali, Mutwakil; Ali, Salem; Ali, Yunusa Y.; et al. (The Lancet (British edition), 2024)
Safe anaesthesia and surgery are a public health imperative. There are few data describing outcomes for children undergoing anaesthesia and surgery in Africa. We aimed to get robust epidemiological data to describe patient care and outcomes for children undergoing anaesthesia and surgery in hospitals in Africa. This study was a 14-day, international, prospective, observational cohort study of children (aged <18 years) undergoing surgery in Africa. We recruited as many hospitals as possible across all levels of care (first, second, and third) providing surgical treatment. Each hospital recruited all eligible children for a 14-day period commencing on the date chosen by each participating hospital within the study recruitment period from Jan 15 to Dec 23, 2022. Data were collected prospectively for consecutive patients on paper case record forms. The primary outcome was in-hospital postoperative complications within 30 days of surgery and the secondary outcome was in-hospital mortality within 30 days after surgery. We also collected hospital-level data describing equipment, facilities, and protocols available. This study is registered with ClinicalTrials.gov, NCT05061407. We recruited 8625 children from 249 hospitals in 31 African countries. The mean age was 6·1 (SD 4·9) years, with 5675 (66·0%) of 8600 children being male. Most children (6110 [71·2%] of 8579 patients) were from category 1 of the American Society of Anesthesiologists Physical Status score undergoing elective surgery (5325 [61·9%] of 8604 patients). Postoperative complications occurred in 1532 (18·0%) of 8515 children, predominated by infections (971 [11·4%] of 8538 children). Deaths occurred in 199 (2·3%) of 8596 patients, 169 (84·9%) of 199 patients following emergency surgeries. Deaths following postoperative complications occurred in 166 (10·8%) of 1530 complications. Operating rooms were reported as safe for anaesthesia and surgery for neonates (121 [54·3%] of 223 hospitals), infants (147 [65·9%] of 223 hospitals), and children younger than 6 years (188 [84·3%] of 223 hospitals). Outcomes following anaesthesia and surgery for children in Africa are poor, with complication rates up to four-fold higher (18% vs 4·4–14%) and mortality rates 11-fold higher than high-income countries in a crude, unadjusted comparison (23·15 deaths vs 2·18 deaths per 1000 children). To improve surgical outcomes for children in Africa, we need health system strengthening, provision of safe environments for anaesthesia and surgery, and strategies to address the high rate of failure to rescue. Jan Pretorius Research Fund of the South African Society of Anaesthesiologists and Association of Anesthesiologists of Uganda.